2015
DOI: 10.3727/096368914x682783
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold High-Frequency Electrical Field Stimulation Induces VEGF Expression in Cardiomyocytes

Abstract: Subthreshold electrical stimulation (SES) has been shown to induce an improvement of angiogenesis in ischemic and nonischemic skeletal muscles, mediated by increased VEGF expression. VEGF plays a key role in physiological and pathological angiogenesis. Cardiomyocytes possess the ability to synthesize and secrete VEGF. Thus, we thought to investigate the effect of SES on VEGF regulation in cultured neonatal rat ventricular myocytes (NRVMs), in the aim to reveal new techniques for therapeutic angiogenesis in isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Moreover, as we all known, VEGF is a highly specific pro-vascular endothelial growth factor with strong ability to promote vascular proliferation. 22 Interestingly, we observed that the proliferation of HCAECs induced by rhMYDGF was almost similar to that of VEGF treatment, and its EC 50 was 7.09 ± 0.04 ng/ mL. Notably, the results of the three independent experimental assays (CCK8, BrdU and MTT assays) for cell proliferation showed that…”
Section: Mitogenic Activity Of Rhmydgf On Hcaecsmentioning
confidence: 62%
“…Moreover, as we all known, VEGF is a highly specific pro-vascular endothelial growth factor with strong ability to promote vascular proliferation. 22 Interestingly, we observed that the proliferation of HCAECs induced by rhMYDGF was almost similar to that of VEGF treatment, and its EC 50 was 7.09 ± 0.04 ng/ mL. Notably, the results of the three independent experimental assays (CCK8, BrdU and MTT assays) for cell proliferation showed that…”
Section: Mitogenic Activity Of Rhmydgf On Hcaecsmentioning
confidence: 62%
“…25 This result suggests electrical stimulation can induce angiogenesis through VEGF production. 25 Because electricity induces cardiac maturity, many clinical cell therapy and tissue engineering research methods apply electrical stimulation paradigms. Skeletal progenitor cells, used for cell therapy, respond to electrical pacing similarly to cardiac cell types.…”
Section: Serena Et Al Electrically Stimulated Human Embryoid Bodies mentioning
confidence: 94%
“…24 Calcium signaling is complemented by VEGF production in the mechanistic response to electrical pacing, and this VEGF production can induce angiogenesis in immature cardiac cells. 25 Rackauskas et al, utilizing subthreshold high-frequency electrical field stimulation on NVRMs, induced secretion and protein expression of VEGF. 25 Furthermore, VEGF secretions into the cell media promoted proliferation of human coronary artery endothelial cells, promoting angiogenesis.…”
Section: Serena Et Al Electrically Stimulated Human Embryoid Bodies mentioning
confidence: 99%
See 2 more Smart Citations